A comparative usability study of two touchscreen clinical workstations for use in low resource settings (Journal of Health Informatics in Africa, 2018)
Cost of implementation is one of the biggest barriers to scale up and sustainability of electronic medical record systems in low resource settings. Several approaches can be used to overcome this barrier. In this comparative usability study, we assess whether a lower cost 10-inch touchscreen clinical workstation (TCW) is a suitable alternative to a 14-inch TCW that has been widely deployed in Malawi. A total of 27 participants performed a patient registration task using three different TCWs, a 14-inch device and two 10-inch devices. One of the 10-inch devices used the same size of interface controls as the 14-inch TCW with reduced space between buttons, and the 10-inch device used a modified interface with controls shrunk down to accommodate the smaller screen size. We measured task completion times and error rates as metrics for assessing performance with each workstation. We also captured user perceptions using a usability survey and an exit survey. We compared the mean task completion time, number of errors, and survey scores between the three devices. In addition, a codebook was created to conduct a thematic analysis of the free-text responses to the exit survey. Our results suggest that the 10-inch TCW is a suitable alternative to the 14-inch TCW based on task completion time. Nonetheless, modifications to the user interface are necessary to reduce error rates on the 10-inch TCW before implementation.